RUANG EDUKASI ANAK-ANAK - Denisa Sumardi Sumardi; Sidhi Wiguna Teh (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2022)
The educational process of children cannot be separated from them need to play, education is a very important activity for children. Through learning, children will get to know the world around them. In Indonesia, the quality of education is still relatively low. In the HDI (Human Development index) survey, Indonesia is ranked 35 out of 57 countries. So the need for a new strategy to improve the quality of education, through programs, new learning methods. Adapting to the behavior and habits of children. Typological methods related to interactive and recreational spaces related to personal, social and public spaces that are prioritized for children. The result is a new education system with the management of open spaces, playrooms and interacting with children. By implementing interactive science, math, art learning programs for children. This research aims to offer a typology of comfortable educational places, taking into account the ergonomics of habits, children's behavior and new experiences for children. As well as analytical studies to develop the relationship between typology and architectural psychology. The children's education room must also provide comfort such as a playground but still maintain the function of an educational place itself Keywords:  Children; Education; Typology.AbstrakProses edukasi anak-anak tidak dapat dipisahkan dengan kebutuhannya akan bermain, edukasi merupakan sebuah aktivitas yang kerusial untuk anak-anak. Melalui belajar, anak akan mengenal dunia sekitarnya. Di Indonesia kualitas Pendidikan masih tergolong rendah. Dalam survei HDI (Human Development index) Indonesia berada di peringkat 35 dari 57 negara. Sehingga perlunya strategi baru peningkatan kualitas edukasi, melalui program, metode balajar yang baru. Menyesuaikan dengan perilaku dan kebiasaan anak-anak. Metode tipologi terkait ruang interaktif dan rekreatif terkait ruang personal, sosial dan publik yang di utamakan untuk anak-anak. Hasilnya adalah system edukasi yang baru dengan pengelolaan ruang terbuka, ruang bermain dan berinterasi anak-anak. Dengan menerapkan program pembelajaran sains, matematika, seni yang interaktif kepada anak-anak. Penelitian ini bertujuan untuk menawarkan tipologi tempat edukasi yang nyaman, dengan memperhatikan ergonomi kebiasaan, tingkah laku anak-anak dan pengalaman baru untuk anak-anak. Serta studi analisis untuk mengembangkan relasi antara tipologi dengan psikologi arsitektur. Ruang edukasi anak-anak juga harus memberikan kenyamanan seperti taman bermain tetapi tetap mempertahankan fungsi dari sebuah tempat edukasi itu sendiri.